The More We Know about the Fundamental, the Less We Agree on the Price - Kondor, Péter (Review of Economic Studies, 2012)
I allow trading horizon heterogeneity across groups in a standard differential information model of a financial market. This approach can explain the well-established phenomenon that, after a public announcement, trading volume increases, more private information is incorporated into prices and volatility increases. In such environments, public information has the important secondary role of helping agents learn about the information of other agents. Therefore, whenever the correlation between the private information of different groups is sufficiently low, a public announcement increases disagreement among short-horizon traders regarding the expected selling price even as it decreases disagreement about the fundamental value of the asset. Additional testable implications are also suggested.